A vinyl cyclopropane ring expansion and iridium‐catalyzed hydrogen borrowing cascade - Wübbolt, S; Cheong, CB; Frost, JR; Christensen, KE; Donohoe, TJ (Wiley, 2020)
A vinyl cyclopropane rearrangement embedded in an iridium‐catalyzed hydrogen borrowing reaction enabled the formation of substituted stereo‐defined cyclopentanes from Ph* methyl ketone and cyclopropyl alcohols. Mechanistic studies provide evidence for the ring‐expansion reaction being the result of a cascade based on oxidation of the cyclopropyl alcohols, followed by aldol condensation with the pentamethyl phenyl‐substituted ketone to form an enone containing the vinyl cyclopropane. Subsequent single electron transfer (SET) to this system initiates a rearrangement, and the catalytic cycle is completed by reduction of the new enone. This process allows for the efficient formation of diversely substituted cyclopentanes as well as the construction of complex bicyclic carbon skeletons containing up to four contiguous stereocentres, all with high diastereoselectivity.